A PROCESS OF SEAMLESSLY REPLACING CG ELEMENTS INTO LIVE-ACTION FOOTAGE - Zhi, Jin (European Scientific Journal, ESJ, 2013)
This research focused on inserting a computer-generated element into live-action footage and replacing unwanted existing objects in the footage. In addition, creating a realistic and seamless visual representation in the field of digital compositing. The purpose of this paper is to cover a detailed working process of digital compositing in order to clarify the production process and provide a clear idea for those entry-level artists to improve an overall understanding of the digital compositing and visual effects and hopefully inspire further collaboration and participants particularly between academia and industry.